Reflexiones sobre la no transferibilidad de los derechos de uso de agua en el Perú - Ruesta Otoya, Favio (2022)
In Peru, access to natural water sources and the rights related to them, are regulated through licenses, permits and authorizations, which are often non-transferable. In contrast with other licenses in the legal system, in order to transfer them a specific process is required.This paper analyses the characteristics of water rights and raises a revision on the specific process needed for their transfer.